Alemtuzumab in a Large Real-Life Cohort: Interim Baseline Data of the TREAT-MS Study - Ziemssen, Tjalf; Hoffmann, Frank; Richter, Stephan; Engelmann, Ulrich; White, Robin (Frontiers in Neurology, 2021)
The TREAT-MS study collects the so far largest real-life cohort regarding utilisation, long-term effectiveness and safety of alemtuzumab, a humanized monoclonal antibody directed against the cell surface glycoprotein CD52, in adult patients with active relapsing-remitting multiple sclerosis (RRMS). An interim analysis of baseline parameters at inclusion of a non-interventional real-world study about alemtuzumab in Germany including previous multiple sclerosis (MS) medication utilisation, MS activity, severity and duration as well as comorbidities was performed. 71.6% of the 883 patients were women. Mean age was 35.7 ± 9.2 years, time since first MS symptoms (= disease duration) 8.0 ± 6.8 years, Expanded Disability Status Scale (EDSS) 2.7 ± 1.8 points (range 0.0 to 7.5 points). The number of relapses in the 12 months and 24 months prior to inclusion were 1.6 ± 1.2 and 2.2 ±1.8, respectively. 14.4% of patients were treatment-naïve, while for the majority a wide spectrum of MS disease modifying treatments (DMT) and treatment sequences were documented. Overall, interferon beta (IFN-beta) was reported most frequently (52.4%), followed by fingolimod (35.2%), natalizumab (34.9%) and glatiramer acetate (28.9%). Patients with longer disease duration and higher EDSS had a higher number of previous DMTs. Compared to the pivotal phase 2/3 studies, RRMS patients starting alemtuzumab treatment had a longer disease duration in real world conditions. There was variety of different treatment sequences before the final switch to alemtuzumab. In the future, linking these treatment sequences or other baseline characteristics with effectiveness and safety outcomes might be useful to support treatment decisions. Registered at Paul-Ehrlich-Institut under NIS 281.